KESETARAAN GENDER DALAM FIKIH PEREMPUAN PERSPEKTIF MAQASID SYARIAH JASSER AUDA - Mohammad Lukman Chakim; habib, Muhammad Habib Adi Putra (MAQASHID, 2022)
The dynamics of today's civilization are growing, it continues to drive changes significantly, both in the technological and other spheres. Existing social construction has shifted, and even needs to be updated to keep up with developments. This includes the role and position of women. In the past, women in the discussion of jurisprudence were only about worship, the treatment of worship that there were differences with men. For example, if the congregation, men are encouraged to read Subhanallah while women pat both palms. But now the discussion of women is getting wider to their roles, positions and relationships with men. This research focused on the gender equality thinking of Husein Muhammad and Musdah Mulia. This research is a normative research (library research) with research sources including several books by Husein Muhammad, Musdah Mulia and Jasser Auda. The thinking of gender equality (women's jurisprudence) of the two figures was then analyzed with Jasser Auda's system (maslahah) approach. The gender equality of women's jurisprudence in the perspective of the Jasser Auda system has conformity with Islamic law. The gender equality of women's jurisprudence has fulfilled all six systems of features (benefits). In the cognitive system, equality has a cognitive conformity capable of uncovering the meaning or practical implications of Islamic law. The argumentation of women's jurisprudence was also adopted from the powerful nash texts, this corresponded to the system of wholeness. Thus with the system of openness and interrelationship, which demands to open wide the thinking of equality to respond to the development of the times. Gender equality view Women's jurisprudence provides answers to these changes in a measured and directed manner, so that Islamic law is always contextual based on the multidimensional system and the meaning of Jasser Auda.